2009
DOI: 10.1074/jbc.m109.027326
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model for Phenylalkylamine Binding to L-type Calcium Channels

Abstract: Phenylalkylamines (PAAs), a major class of L-type calcium channel (LTCC) blockers, have two aromatic rings connected by a flexible chain with a nitrile substituent. Structural aspects of ligand-channel interactions remain unclear. We have built a KvAP-based model of LTCC and used Monte Carlo energy minimizations to dock devapamil, verapamil, gallopamil, and other PAAs. The PAA-LTCC models have the following common features: (i) the meta-methoxy group in ring A, which is proximal to the nitrile group, accepts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 61 publications
1
49
0
2
Order By: Relevance
“…Molecular modeling suggested that these amino acid residues face the lumen of the pore and cooperate to form the drug-binding site (Cheng et al, 2009). In agreement with these prior molecular models, the three-dimensional structure of CavAb places these amino acid residues in positions to cooperate in forming a single drug-binding site in the central cavity of the pore (Fig.…”
Section: Receptor Sites For Calcium Antagonist Drugssupporting
confidence: 79%
See 2 more Smart Citations
“…Molecular modeling suggested that these amino acid residues face the lumen of the pore and cooperate to form the drug-binding site (Cheng et al, 2009). In agreement with these prior molecular models, the three-dimensional structure of CavAb places these amino acid residues in positions to cooperate in forming a single drug-binding site in the central cavity of the pore (Fig.…”
Section: Receptor Sites For Calcium Antagonist Drugssupporting
confidence: 79%
“…Molecular modeling and ligand-docking methods have been used to predict the binding pose of the phenylalkylamines in their receptor site (Lipkind and Fozzard, 2003;Cheng et al, 2009). In the initial study, based on the structure of the KcsA potassium channel, the bound phenylakylamine was fit in a half-folded, L-shaped conformation, with the positively charged ammonium group projecting toward the negatively charged ion selectivity filter, aromatic ring A in the central cavity, and aromatic ring B projecting toward the interface between domains III and IV (Lipkind and Fozzard, 2003).…”
Section: Receptor Sites For Calcium Antagonist Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the demethoxylated phenyl ring B of emopamil can penetrate the intersubunit niche of the mutant. In a model of devapamil in the Ca v 1.2 channel intra-and interdomain interfaces constitute binding loci for rings A and B, respectively (Cheng et al, 2009). Why does ring B of devapamil bind between helices 3P and 4S6 in Ca v 1.2, but does not bind between respective helices in Kv1.3?…”
Section: Discussionmentioning
confidence: 99%
“…S6s from neighboring subunits line four interfaces. In homology models of sodium and calcium channels, corresponding interfaces between domains III and IV contain residues whose mutations affect access and binding of different ligands (Zhorov and Tikhonov, 2004;Bruhova et al, 2008;Tikhonov and Zhorov, 2008;Cheng et al, 2009). Extracellularly applied permanently charged compounds, which cannot permeate the membrane, were proposed to reach their binding sites within the inner pore through the III/IV domain interface (Tikhonov et al, 2006;Bruhova et al, 2008;Tikhonov and Zhorov, 2008).…”
Section: Introductionmentioning
confidence: 99%